Answer:
John: 10
Fred: 5
Explanation:
We can solve this like a system of equations.
Set Variables:
John: j
Fred: f
Given Info:
2f = j
j - 4 = 6(f - 4)
Use the distributive property, a(b+c) = ab+ac to simplify.
j - 4 = 6f - 24
Use info from the first equation and substitute.
j - 4 = 6f - 24
2f = j
6f = 3j
j - 4 = 3j - 24
Add 24 on both sides.
j - 4 + 24 = 3j - 24 + 24
j + 20 = 3j
Subtract j on both sides.
j - j + 20 = 3j - j
20 = 2j
Divide 2 on both sides.
j = 10
Because j is twice f, divide 10 by 2 to get f.
10/2 = 5